Relationship between unionized companies, government ownership and reporting human capital information in corporate annual reports - Mara Ridhuan Che Abdul Rahman; Mohammed Ahmed, Rebwar; Mohamat Sabri Hassan (Penerbit Universiti Kebangsaan Malaysia, 2017)
Investors, employees, and societies are interested in human capital information. This information will assist investors to assess the effectiveness of human capital management to deliberate their investment capital allocation. The employees will also know the extent of their development and value in organizations. Despite the significant role of human capital in the success and survival of an organization, human capital information disclosure is still limited in annual reports. Thus, investors or other stakeholders have scarce information to distinguish between organizations that develop human capital and those that constrain human capital. The factors that explain the disclosure is still unknown. In light of stakeholder’s theory, this study investigated the relationship between highly unionized companies and government-owned companies, which are factors that can pressure companies to disclose human capital information in annual reports. Companies from the banking and financial institution industries were selected as highly unionized companies, whereas companies from the real property industry were selected as poorly unionized companies based on the Malaysian Trade Union Congress (MTUC) dataset. Government ownership was also identified in these sample companies. A total of 192 annual reports gathered from 48 companies for the financial year from 2010 to 2014 were analyzed in terms of content. Control variables, such as age, size, profit, and leverage, were also associated in the relationship. This study determined that highly unionized companies (banks) and government ownership demonstrate significantly positive relationship with human capital information reporting in annual reports. For control variables, only the size of companies shows positive relationship with the disclosure. Therefore, the presence of stakeholders in companies (i.e., union membership and government) is considered a good predictor for reporting human capital information in annual reports.